Odnos do jezika in dvojezičnosti pri dijakih na dvojezičnem italijansko-slovenskem območju v Italiji - Ožbot, Martina (Jezik in slovstvo, 2021)
The paper reports the findings of a questionnaire-based study of high school pupils from Slovenian and Italian state secondary schools in the bilingual areas of Gorizia/Gorica and Trieste/Trst. Over the past years, there has been some rapprochement between the two principal ethnic communities, the Italian majority and the Slovenian minority, which can be perceived, among other things, in a heightened interest in Slovenian language and culture among the majority Italian community. The questionnaire, which focuses on three topics (pupils' linguistic identity, their view of an ideal language situation, and their attitude towards bilingualism and multilingualism), reveals that the two groups of pupils have more common points than points of divergence. Both groups are well aware of the importance of a knowledge of languages and of the value of bilingualism. Understandably, the views of pupils from Slovenian schools are more influenced by the local situation, in which they feel more urgently the need for the minority language to be represented. Some stereotypical perceptions of the Other persist, but on the whole it appears that the local environment is characterised by a significant openness towards and interest in the Other.
Keywords: bilingualism; dvojezičnost; Italian; Italian state secondary schools; Italija; italijanske državne srednje šole; italijanščina; Italy; language attitude; odnos do jezika; Slovenian; Slovenian state secondary schools; slovenske državne srednje šole; slovenščina; zamejstvo